Cognitive linguistic studies: a global diversity - Shevchenko, Iryna (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2018)
The article covers the highlights of Ukrainian linguists’ participation in the International Cognitive Linguistics Conference “Linguistic Diversity and Cognitive Linguistics” (ICLC-14, 1–14 July 2017, Tartu, Estonia).